PEMBUATAN WEBSITE PELAYANAN KESEHATAN IBU DAN ANAK DI PUSKESMAS SIANTAN TENGAH KOTA PONTIANAK - Safri Adam; Elsa Noftalina (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
The Puskesmas of Siantan Tengah sub-district in Pontianak City is part of the organizational structure of the Pontianak City Health Office, which carries out health services for the community. Maternal and child health is of particular concern at Central Siantan Public Health Center, including health information services. However, at the time of the Covid-19 pandemic there was a decline in services due to people's fear of visiting the puskesmas. To solve this problem, various efforts have been made to improve maternal and child health services at the Central Siantan Public Health Center. The advancement of web-based information and communication technology is currently the focus of development. In this case the website can be a means of delivering information to the public. The information presented is in the form of maternal and child health services. With the presence of smartphones in the world today, website-based applications can be accessed via smartphones. With this community service, a website for maternal and child health services is produced which is expected to help improve maternal and child health services. The website can be accessed online, especially pregnant mother can access information related to maternal and child health at home. The conclusion from the results of this community service is that a website for maternal and child health services in the community of Central Siantan sub-district is produced which can help Puskesmas deliver information related to maternal and child health.